Kecerdasan Emosional Pendidik PAUD dalam Membangun Lingkungan Belajar yang Positif - Fauziyah Rizkika; Aini Loita; Nazwa Nabila; Shifa Nur Rohmah; Zahra Aulia Hidayati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The emotional intelligence of early childhood educators is a key factor in creating a positive learning environment that supports early childhood development. This study aims to analyze the role of teachers’ emotional intelligence in fostering a safe, comfortable, and conducive learning atmosphere. The method used was a literature review examining various research findings related to the emotional intelligence of early childhood educators. The results of the review indicate that teachers’ emotional intelligence which encompasses self-awareness, self-regulation, motivation, empathy, and social skills plays a significant role in enhancing the quality of teacher-child interactions, classroom management, and children’s social-emotional development. Furthermore, teachers’ emotional intelligence is also linked to their psychological well-being and children’s learning motivation. The implementation of emotional intelligence in learning can be achieved through empathetic communication, the use of affective language, positive reinforcement, and collaborative play activities. However, there are several challenges, such as high emotional workload and limited teacher-to-student ratios. Therefore, support in the form of training, institutional policies, and the integration of social-emotional learning into the curriculum is needed. Thus, strengthening the emotional intelligence of early childhood educators is a strategic step in creating a learning environment that is not only academically effective but also supports children’s emotional and social development